АКТУАЛЬНІ ПРОБЛЕМИ ВИКЛАДАННЯ ФІТОДШАЙНА (Педагогіка вищої та середньої школи, 2009)
The article considers the role and place of the discipline "Theory and practice of ornamental horticulture and floriculture" in art and pedagogical education. The authors were provided with an indicative program for its teaching in the block of disciplines of the specialty "Fine Art Phytodesign" at the graphic arts department of the Faculty of Arts of Kryvyi Rih State Pedagogical University.